Executive function ability in persons with aphasia - Purdy, M. (Aphasiology, 2002)
Background: There is an increasing recognition that the communication problems one observes in persons with aphasia extend beyond verbal deficits and that the myriad of symptoms observed are not solely due to a faulty linguistic system. Rather, there exists a coalition of causal elements resulting in a wide range of communicative deficits. There is some preliminary evidence suggesting that communicative success of clients with aphasia may depend on the integrity of executive function skills. Executive functions are called into play when an individual is involved in a complex, novel activity. They allow us to plan, sequence, organise, and monitor goal-directed activities in a flexible manner as demanded by situational and environmental changes. When linguistic skills are impaired, individuals need to rely on other cognitive skills in order to communicate. Aims: The purpose of this study was to explore executive functioning ability in persons with aphasia. Methods & procedures: A total of 15 individuals with aphasia and 12 healthy control subjects participated in this study. Three dimensions of performance were examined (accuracy, speed, and efficiency) in the context of neuropsychological tests designed to examine cognitive flexibility and goal-directed planning (Wisconsin Card Sorting Test, Porteus Maze Test, Tower of London, and Tower of Hanoi). Outcomes & results: Results indicated that the two groups performed with similar levels of accuracy on two of the four tests. However, significant differences were found on all speed and efficiency variables, suggesting decreased executive functioning skills in the group of individuals with aphasia. Conclusions: It is important to consider executive functioning ability in clients with aphasia and attempt to determine the influence of executive function skill on communicative performance. Understanding the cognitive abilities as well as the linguistic abilities of these clients may ultimately help clinicians determine which patients are better candidates for intervention as well as which treatment approaches would be most efficient and beneficial.
108 citations (Crossref) [2023-10-31]
Keywords: Wisconsin card sorting test; accuracy; adult; aged; aphasia; article; clinical article; cognition; communication disorder; comparative study; controlled study; dept.cmd; human; interpersonal communication; language ability; linguistics; maze test; mental function; mental performance; neuropsychological test; peer-reviewed; planning; skill; treatment planning

More than words - Wallace, S.; Purdy, M. (ASHA Leader, 2013)
0 citations (Crossref) [2023-10-31]
Keywords: dept.cmd

Multimodal communication training in aphasia: A pilot study - Purdy, M.; Van Dyke, J.A. (Journal of Medical Speech-Language Pathology, 2011)
Management of patients with aphasia often focuses on training nonverbal augmentative communication strategies; however, these strategies frequently do not generalize to natural situations. The limited success may be because training was not sufficient to produce an integrated multimodal semantic representation. The purpose of this study was to examine whether simultaneous training of stimuli in both verbal and nonverbal modalities would solidify the links within the semantic network and improve switching among modalities as needed in conversation. Two individuals with severe aphasia participated in 6 to 8 hours of Multimodal Communication Training (MCT), during which they conveyed a concept by verbalizing, gesturing, writing, and drawing. After practice with all modalities for a single concept, a new concept was introduced. Results showed that one participant increased conveyance of concepts on the functional communication task using a variety of modalities. Although some improvement was seen with the second participant, his overall performance remained poor, likely because of a greater impairment in semantic knowledge. After a brief period of semantic training, the second participant demonstrated additional gains. Thus, MCT may serve to increase switching among verbal and nonverbal modalities in individuals with intact semantic representations, thereby increasing the likelihood that individuals will use an alternative method to communicate. Copyright © 2011 Delmar Cengage Learning.
Keywords: AAC; Aphasia; Cognition; Multimodality; Treatment; adult; aged; article; ataxic aphasia; case report; communication skill; concept formation; cortical sensory aphasia; dept.cmd; disease severity; drawing; gesture; human; male; multimodal communication training; priority journal; semantic memory; task performance; verbalization; writing; ⛔ No DOI found